The mechanisms of adaptation for muscle fascicle length changes with exercise: Implications for spastic muscle. (November 2020) - Davis, J.F.; Khir, A.W.; Barber, L.; Reeves, N.D.; Khan, T.; DeLuca, M.; Mohagheghi, Amir A.
Abstract: We are proposing optimal training conditions that can lead to an increase in the number of serial sarcomeres (SSN) and muscle fascicle length (FL) in spastic muscles. Therapeutic interventions for increasing FL in clinical populations with neurological origin, in whom relative shortness of muscle fascicles contributed to the presentation of symptoms such as spasticity, contracture, and limited functional abilities, do not generally meet these conditions, and therefore, result in less than satisfactory outcomes. Based on a review of literature, we argue that protocols of exercise interventions that led to sarcomerogenesis, and increases in SSN and FL in healthy animal and human models satisfied three criteria: 1) all involved eccentric exercise at appropriately high velocity; 2) resulted in positive strain of muscle fascicles; and 3) momentary deactivation in the stretched muscle. Accordingly, to increase FL in spastic muscles, new exercise protocols in which the three presumed criteria are satisfied, must be developed, and long-term muscle architectural and functional adaptations to such trainings must be examined.